Paying somatotype to at schoolboys at improvement of their health of process of physical education. - Sidorchenko E. N. (Kharkov National Pedagogical University, 2010)
Roads of improving of health of schoolboys are construed during physical training. It is indicated on necessity of making of proper pedagogical conditions of realization of the differentiated approach during physical training of adolescents. In a basis of the approach the account of their somatotype lays. It is emphasized on a volume, that the somatotype defines physical developing, functionalities of an organism, parameters of physical state. Unequal tendency of the basic somatotypes to different diseases is established. Necessity to supplement medical parameters of health of children of school age is scored by biological measure.